Available Micronutrients in Mixed Red and Black Soils of Rajasthan - Baser, B.L.; Lodha, P.S. (Journal of Soil and Water Conservation, 2022)
Micronutrient studies have not yet received much attention like major nutrients in the country and the information available is quite fragmentary. A comprehensive review presented by Kan war and Randhawa (19671 showed that micronutrient deficiencies occur in various parts of the country. As the demand for higher yields increases and the plant requirements for micronutrients is more efficiently met, the micronutrient deficiencies are likely to become more acute. With increased awareness of crop quality and maxi- mum production the use of micronutrients have assumed much importance to make the fertilizers more balanced so that micronutrients may not become a limiting factor in increasing crop yields and affecting quality of crops, As a first step towards this an assessment of available status of nutrients in soils is a prerequisite. The state of Rajasthan is a tract which has widely different agro-climatic regions and comprises of eight major soil groups. In the present findings mixed red and black soils from Udaipur, Sirohi and part of Chittor districts were investigated for available micronutrient status.